A Study of the Relationship between Organizational Culture and Job Involvement: The Moderating Role of Psychological Conditions of Meaningfulness and Safety - TÜRKER, MALİK VOLKAN; BÜLBÜL, SEÇİL (ELSEVIER SCIENCE BV, 2014)
This study was conducted to examine the relationship between organizational culture and employees' job involvement. Moreover, this study investigated the moderating role of employees' psychological conditions meaningfulness and safety. An empirical study was conducted in Turkey by involving the participation of 264 respondents in banking, insurance and finance organizations. A survey was conducted using the Organizational Culture Questionnaire (OCQ) with the approach of Harrison (1993), the Job Involvement Scale, Psychological Meaningfulness and Psychological Safety Scales to determine the relationships between the variables. The uniqueness of this study considered that the organizational culture construct with the relevant approach was linked to employee work attitude of job involvement in the moderating context of psychological conditions of meaningfulness and safety. The research results were evaluated with its implications of both conceptual and practical levels. (C) 2014 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/3.0/).
Keywords: Organizational culture; Job involvement; Psychological conditions; Psychological meaningfulness; Psychological safety; WORK; ENGAGEMENT; PERSONALITY; BEHAVIOR; CLIMATE